Variation of Al concentrations depending on the growing environment in some indoor plants that used in architectural designs - Cetin, Mehmet; Abo Aisha, Adel Easa Saad (Springer Science and Business Media LLC, 2022)
Today, most of people's time is spent indoors. Air pollution indoors is much higher than outdoors. Therefore, the effect of indoor air on human health is much more than the outside air. One of the most effective methods of reducing indoor air pollution is the use of plants. However, in order for the plants to be used effectively for this purpose, it is first necessary to determine which plants are the most effective in reducing which pollutants. Within the scope of this study, the Al accumulation potential of seven ornamental plants, which are frequently used in interior architectural designs, was evaluated. Within the scope of the study, the variation of Al concentrations on the basis of species and environment was determined in plants grown in control, smoking environment, and traffic environment. As a result of the study, it was determined that Al concentrations changed statistically significantly both on the basis of environment and species, and the species with the highest Al accumulation potential was difenbahya.
Keywords: Air Pollutants; Air Pollution; Air Pollution, Indoor; Humans; Environmental Pollutants; Plants; Environmental Monitoring; 13. Climate action; 11. Sustainability; 6. Clean water